Studying the photocatalytic oxidation of hydroxybenzene in aquatic medium on the photocatalizers SnO2, ZnO, TiO2 - Deineka, Dmytro; Kobziev, Oleksandr; Avina, Svitlana; Grin, Svitlana; Deyneka, Viktoriya; Taraduda, Dmytro; Sobina, Vitaliy (Eastern-European Journal of Enterprise Technologies, 2018)
This paper reports results of research into photocatalytic activity of oxides SnO2, ZnO, TiO2 in the process of hydroxybenzene degradation in an aqueous medium with the separately considered properties of the allotrope modifications of titanium oxide (IV): anatase and rutile. The relationship has been substantiated between a decrease in the value for the width of the restricted area and an increase in the photocatalytic activity of the examined oxides. The effect has been established of the organization of agitation on an increase in the degree of hydroxybenzene degradation in an aqueous medium, which is 10‒15 % on average. We have studied the influence of ratio of anatase to rutile in a photocatalyst on the hydroxybenzene degradation efficiency. It has been shown that the results obtained in the course of the study are consistent with data from the scientific literature, while opening up additional possibilities to increase the degree of hydroxybenzene oxidation in a joint application of anatase and rutile. It was established that the greatest degree of oxidation with and without agitation at an irradiation time of 60 minutes can be achieved at the content ratio of anatase to rutile of 75/25 % and is 23 % and 37 %, respectively. The use of such a composition makes it possible to increase the degree of hydroxybenzene oxidation in an aqueous medium by 11‒18 %, which is 1.5‒1.9 times larger in comparison with pure rutile and anatase. The results obtained led to the conclusion on that in order to reduce the time required to achieve the maximal indicators for the process of hydroxybenzene degradation, it is necessary to increase the ratio of the irradiated surface to the height of the device and to increase the Re number of the agitation process. Based on the obtained experimental data, we have established the optimum composition of a photocatalyst, which makes it possible to reach the maximal degree of hydroxybenzene recovery from solution